Constructing a standardized Multi-Criteria Tender Evaluation for IT projects using Balanced Scorecard - Baharom F.; Muhd Darus N.; Mohd H.; Mat Kasim M.; Marzuki Matt Z.; Md Nawawi N. (2024)
Indexed by Scopus